Enhanced photocatalytic activity of S-doped BiVO4 photocatalysts. Issue 72 (6th August 2015) - Guo, Minna; Wang, Yang; He, Qianglong; Wang, Wenjie; Wang, Weimin; Fu, Zhengyi; Wang, Hao
<x xml:space="preserve">Abstract</x> We synthesized S-doped BiVO4 photocatalysts, and they exhibit an enhanced degradation efficiency of MB at 100% after 25 min under visible-light irradiation.